Pengaruh Kompetensi Sumber Daya Manusia, Penerapan Sistem Akuntansi, Pemanfaatan Teknologi Informasi Dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Realisasi Anggaran - Ramadani Hesti Kusuma; Noor Endah Cahyawati (Jurnal Manajemen Riset Inovasi, 2024)
This research aims to determine whether human resource competence, application of accounting systems, use of information technology and internal control systems influence the quality of budget realization reports at PT. X. This research was conducted involving 40 employees of PT X who were directly involved in the budget process and preparation. Research data was obtained from questionnaires distributed to respondents. Questionnaire data was processed using the IBM SPSS Statistics application. The analytical method used is multiple linear regression analysis. The results of the analysis show that human resource competency does not influence the quality of the budget realization report, meanwhile the application of the accounting system, use of information technology and the internal control system influence the quality of the budget realization report.